Digital Piracy in the Western Balkans with a special reference to North Macedonia - Atanasovski, Simon; Sherifi, Diellza; Gramatikov, Sasho (My University, 2022)
This paper is a brief attempt to understand the current situation with digital piracy on the territory of the Western Balkans with special reference to the situation in North Macedonia. Digital piracy is a state of owning, using, copying, and distribution of copyrighted material without the permission of its owner. As a phenomenon, piracy has long time been a global problem, which, among other things, causes great material losses to many individuals, and private entire industries. Especially affected are the software industry, music, film, and other industries. For the purposes of this paper, a survey was conducted regarding the use, prevalence, ways, causes, and awareness of the legal consequences of the use of pirated materials in our country. The results of our work should lead to possible directions for further action in order to reduce this problem.
Keywords: Digital piracy, Intellectual property, copyright, ethics